Novel Strategy for Generation and Titration of Recombinant Adeno-Associated Virus Vectors - Shiau, Ai-Li (American Society for Microbiology, 2005)
Recombinant adeno-associated virus (rAAV) vectors have many advantages for gene therapeutic applications compared with other vector systems. Several methods that use plasmids or helper viruses have been reported for the generation of rAAV vectors. Unfortunately, the preparation of large-scale rAAV stocks is labor-intensive. Moreover, the biological titration of rAAV is still difficult, which may limit its preclinical and clinical applications. For this study, we developed a novel strategy to generate and biologically titrate rAAV vectors. A recombinant pseudorabies virus (PrV) with defects in its gD, gE, and thymidine kinase genes was engineered to express the AAV rep and cap genes, yielding PS virus, which served as a packaging and helper virus for the generation of rAAV vectors. PS virus was useful not only for generating high-titer rAAV vectors by cotransfection with an rAAV vector plasmid, but also for amplifying rAAV stocks. Notably, the biological titration of rAAV vectors was also feasible when cells were coinfected with rAAV and PS virus. Based on this strategy, we produced an rAAV that expresses prothymosin α (ProT). Expression of the ProT protein in vitro and in vivo mediated by rAAV/ProT gene transfer was detected by immunohistochemistry and a bioassay. Taken together, our results demonstrate that the PrV vector-based system is useful for generating rAAV vectors carrying various transgenes.